2009
DOI: 10.1101/gr.096651.109
|View full text |Cite
|
Sign up to set email alerts
|

The NIH Human Microbiome Project

Abstract: The Human Microbiome Project (HMP), funded as an initiative of the NIH Roadmap for Biomedical Research (http://nihroadmap.nih.gov), is a multi-component community resource. The goals of the HMP are: (1) to take advantage of new, high-throughput technologies to characterize the human microbiome more fully by studying samples from multiple body sites from each of at least 250 “normal” volunteers; (2) to determine whether there are associations between changes in the microbiome and health/disease by studying seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
982
0
21

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,761 publications
(1,010 citation statements)
references
References 29 publications
7
982
0
21
Order By: Relevance
“…The development of tools for high throughput DNA sequencing and computational support for the vast data sets thus generated has overcome the limitation of previous culture-based microbiological studies of the human skin (Leyden et al, 1981(Leyden et al, , 1987Kearney et al, 1984;Roth and James, 1988;Chiller et al, 2001), and has renewed interest in the characterization of the human cutaneous microbiome using culture-independent techniques (Dethlefsen et al, 2007;Oakley et al, 2008;Avila et al, 2009;Hamady and Knight, 2009;Nasidze et al, 2009;Peterson et al, 2009;Turnbaugh et al, 2009;Zhang et al, 2009;Qin et al, 2010). Investigators now are using molecular, DNA-based methodologies to assess the microbial populations present in and on human skin (Fredricks, 2001;Paulino et al, 2006Paulino et al, , 2008Gao et al, 2007Gao et al, , 2008Gao et al, , 2010Fierer et al, 2008Fierer et al, , 2010Grice et al, 2008Grice et al, , 2009Costello et al, 2009;Grice and Segre, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of tools for high throughput DNA sequencing and computational support for the vast data sets thus generated has overcome the limitation of previous culture-based microbiological studies of the human skin (Leyden et al, 1981(Leyden et al, , 1987Kearney et al, 1984;Roth and James, 1988;Chiller et al, 2001), and has renewed interest in the characterization of the human cutaneous microbiome using culture-independent techniques (Dethlefsen et al, 2007;Oakley et al, 2008;Avila et al, 2009;Hamady and Knight, 2009;Nasidze et al, 2009;Peterson et al, 2009;Turnbaugh et al, 2009;Zhang et al, 2009;Qin et al, 2010). Investigators now are using molecular, DNA-based methodologies to assess the microbial populations present in and on human skin (Fredricks, 2001;Paulino et al, 2006Paulino et al, , 2008Gao et al, 2007Gao et al, , 2008Gao et al, , 2010Fierer et al, 2008Fierer et al, , 2010Grice et al, 2008Grice et al, , 2009Costello et al, 2009;Grice and Segre, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators now are using molecular, DNA-based methodologies to assess the microbial populations present in and on human skin (Fredricks, 2001;Paulino et al, 2006Paulino et al, , 2008Gao et al, 2007Gao et al, , 2008Gao et al, , 2010Fierer et al, 2008Fierer et al, , 2010Grice et al, 2008Grice et al, , 2009Costello et al, 2009;Grice and Segre, 2011). However, these studies were all performed in humans who live in developed countries, as does the large-scale National Institute of Health (NIH)-initiated Human Microbiome Project (Peterson et al, 2009), that shares this focus on humans living lifestyles associated with postmodern socioeconomic development. The microbiota in normal persons in developed countries has likely been substantially altered by changes associated with socioeconomic development, including frequent showering, and use of soap, cosmetics and antibiotics (Blaser and Falkow, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At Visit 1 (Day −14 to −7), all participants undertook informed consent and received study materials. The Lifestyle Questionnaire was based on the American Gut arm of the Human Microbiome Project 15. The seven‐day food diary was provided by the Human Nutrition Unit (HNU), University of Auckland, New Zealand.…”
Section: Methodsmentioning
confidence: 99%
“…The largest microbial community resides in the gut, where microbial cells and their genes outnumber human cells (10:1) and genes (100:1) (Peterson et al ., 2009; Zhu et al ., 2010; The Human Microbiome Project 2014a). More than 10 000 different species with millions of protein‐coding genes were identified by the Human Microbiome Project (Turnbaugh et al ., 2007; Peterson et al ., 2009; Biagi et al ., 2012) and >1000 of these microbes have so far been fully sequenced (The Human Microbiome Project 2014b). Although twin studies have found a modest genetic influence on some phyla, most of the variation is environmental (Goodrich et al ., 2014).…”
Section: Omics and Agingmentioning
confidence: 99%